The Effect of the Implementation of the Contextual Teaching and Learning (CTL) Model Assisted by Animation Videos on the Learning Outcomes of Science and Social Studies (IPAS) for 4th-Grade Students at SDN 01 Pulau Punjung - Hasibuan, Rusdi Indra; Ratnawati, Ratnawati; Putri, Amelia (The Future of Education Journal, 2025)
The issue faced in the 4th-grade class during the learning process is that students’ understanding of the lesson material is still lacking. Even though a learning model is being used, its implementation has not been maximized. This study aims to examine the effect of audiovisual media using the Contextual Teaching and Learning (CTL) model with the assistance of animation videos on the learning outcomes of Science and Social Studies (IPAS) for 4th-grade students at SDN 01 Pulau Punjung. This is a quantitative study using an experimental approach with a quasi-experimental design. The research method used is the Nonequivalent Control Group Design. The population in this study consists of all students in 4th-grade classes IV-A and IV-B. The sample consists of 32 students, with 20 students in class IV-A and 12 students in class IV-B. The experimental group was class IV-A, and the control group was class IV-B. The data collection technique used in this study was a test in the form of objective questions. Learning outcomes were measured by conducting tests twice, before (pre-test) and after using the CTL model assisted by animation videos (post-test). The research was conducted in the 2025/2026 academic year. Based on the results of the Independent Samples Test, the significance value obtained was 0.002. Since the significance value of 0.002 is less than 0.05, the paired sample t-test results show that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is a significant effect of the implementation of the Contextual Teaching and Learning model assisted by animation videos on the learning outcomes of IPAS for 4th-grade students at SDN 01 Pulau Punjung.